AYURVEDIC MANAGEMENT OF ARDITA (BELLS PALSY): A CASE STUDY - Dr, *Shikha; Priyanka, Rani; Renu, Rao; Mohan, Kumar (International Journal of Ayurveda and Pharma Research, 2017)
Ardita is considered as one among the Vata Nanatmaja Vyadhis described in our Ayurvedic classics. It can be correlated with the disease Bells Palsy in modern aspects. The present study was conducted with an objective to find out the effective Ayurvedic management in Bells palsy. For present study, a 28 years old Hindu male having history of watering from right eye, difficulty in closing right eye, difficulty in moving up right eyebrow, difficulty in moving up right eyebrow with uneven frequency since last 5 years was registered in our OPD. History and examinations lead to the diagnosis of idiopathic facial nerve paralysis i.e. Bells palsy. Considering the signs and symptoms patient was treated on the lines of Ardita Chikitsa. Nasya Chikitsa with Bala Bilva Ghrita, Tarpana with Jeevantyadi Ghrita, Karnapoorana with Ksheer- Bala Taila were done along with oral drugs and exercise. 100% relief was found in watering from eyes, slurring of speech, dribbling of saliva from right corner of mouth (Lalasrava), earache (Karnshool). 75% relief was found in trapping of food between gums and cheek. 50% relief was found in widening of palpebral aperture (Netra Vikriti), absence of Nasolabial fold and in smiling sign. Before starting the treatment the House Brackmanns grading of facial nerve was Grade 4 and after commencement of 28 days treatment it was Grade 2. There was no side effect observed during and after the treatment.